Influence of nano-polystyrene on cyfluthrin toxicity in honeybee Apis cerana cerana Fabricius - Yunfei Xue; Xueyang Gong; Linfu Yang; Dandan Zhi; Qingxin Meng; Yulong Guo; Kun Dong; Yakai Tian (Ecotoxicology and Environmental Safety)
Plastics and pesticides are commonly used and often coexist in the environment. As pollinating insects, honeybees are simultaneously exposed to both these toxins. However, there has been no study on the toxic effects of nano-polystyrene plastics (nanoPS) and cyfluthrin (Cy) on the Apis cerana cerana Fabricius until now. This study found that nanoPS did not significantly impact the mortality of Apis cerana cerana but could reduce cyfluthrin-induced mortality. Additionally, nanoPS caused damage to the honeybee gut and hindered the development of the hypopharyngeal glands, whereas cyfluthrin did not produce these pathological changes. Concerning the detoxification-related genes, the two toxins alone and in combination significantly promoted the expression of P450 9E2 and Cyp9Q3 genes, and the upregulation trend was found more significant for the combination. Regarding immune gene expression, exposure to a single toxin or both toxins significantly down-regulated the abaecin gene, but only exposure to nanoPS significantly decreased apidaecin expression. The changes in metabolites and metabolic pathways in honeybees after ingesting nanoPS were also studied. This study highlights the toxicity of nano-microplastics and Cy alone and in combination to Apis cerana cerana Fabricius and provides new insights into the potential ecological risks of nanoPS.